Parametric optimization for hardness of tig welded duplex stainless steel - Mondal, Sandip; Kumar Bose , Goutam (International Journal of Industrial Optimization, 2023)
Achieving optimal mechanical properties in welding joints hinges on employing precise parametric conditions. This is particularly crucial for Tungsten Inert Gas (TIG) welding of ASTM/UNS 2205 Duplex Stainless Steel (DSS), where attributes like hardness, ultimate tensile strength, and yield strength are paramount. Maintaining high Hardness Value (HV) demands proper welding parameters such as welding current, gas flow rate, and welding speed. To enhance DSS welding quality, especially hardness, this study utilizes the Taguchi method to optimize welding process parameters. The importance of each factor is assessed through Annova statistical analysis. The outcomes highlight the positive impact of parametric optimization on HV, as evidenced by the analysed data. Parametric optimization proves to be a potent approach for refining industrial processes like welding, with particular relevance in TIG welding of duplex stainless steel due to its mechanical robustness and corrosion resistance. Nevertheless, challenges arise due to the material's elevated hardness and low thermal conductivity, resulting in potential defects like cracks and porosity. The identification of optimal welding parameters, encompassing current, voltage, speed, and gas flow rate, helps address these challenges and advances high-quality welds. Through systematic variations and analysis of these parameters, researchers and engineers can pinpoint the optimal combination that mitigates defects while maximizing desired joint attributes. Within the realm of TIG welding of duplex stainless steel, metric optimization holds the potential to elevate welding quality, curtail costs and waste, and heighten productivity and safety. Consequently, organizations can attain enhanced performance, efficiency, and profitability within their welding processes